MAKING BIODIESEL FROM RAW MATERIALS CPO (CRUDE PALM OIL) TRENCHES WITH DEGUMMING METHOD AND ANALYSIS BASED ON SNI 04-7182-2006 - Gerda Pintoko Tunjungsari; Muhamad Aditya Hidayah; Hisyam Mashadi (JARES (Journal of Academic Research and Sciences), 2021)
Palm oil liquid waste or waste processing CPO (Crude Palm Oil) commonly called CPO (Crude Palm Oil) trenches are very potential to be processed into biodiesel. At the moment, CPO (CPO trenches) processing waste is only considered as waste that pollutes the environment and is not of economic value. If left continuously, palm oil liquid waste that has a pH of 4.2 (acidic) will cause problems for the environment if disposed of directly. One form of utilization of CPO trenches that can be done is by converting it into biodiesel. The manufacture of biodiesel from CPO trenches uses transesterification reactions such as the manufacture of biodiesel in general, with pretreatment to lower the acid figures in the CPO trenches. Biodiesel was obtained later in the analysis of quality standards based on SNI 04-7182-2006 and obtained results that meet the requirements for four parameters, namely the content of FFA samples before the transesterification process is 1.82%. Tan biodiesel content of 0.3055 mg KOH/g. The content of free glycerol is 0.0198% and the total glycerol is 0.0884%.